MONITORING PARAMETER AIR BERBASIS IOT (INTERNET OF THINGS) - Anshori, Yusuf; Parenrengi, Andi Fathur Alamsyah A.; Angreni, Dwi Shinta; Ardiansyah, Rizka; Joefrie, Yuri Yudhaswana (Foristek, 2023)
Water is a necessity for living things that have certain parameters to be consumed. This tool is made to measure the parameters of pH, temperature and turbidity of water quality and this tool is integrated with Internet of Things (IoT) technology so that sensor measurement data can be accessed anywhere and anytime. This tool implements Fuzzy Logic to generate “clean” and “unclean” values for water and uses the NodeMCU-ESP32s Module as the main controller, the PH-4502c sensor measures pH, the SKUSEN0189 sensor measures turbidity, and the DS18B20 sensor measures temperature. The results show that all sensors work well with an average error value of 2.95% for pH, 0.80% for temperature, and 21.32% for turbidity.